2007
DOI: 10.3923/pjbs.2007.421.426
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Deficit on Yield and Yield Components of Safflower (Carthamus tinctorius L.)

Abstract: The aim of this study carried out in Shahid Chamran Ahwaz, University, in 2001-2002 to determine the effect of different forms of irrigation on the safflower (Carthamus tinctorius L.) yield and yield components. Information was needed on application time of irrigation water on cultivars of safflower (Carthamus tinctorius L.). Increasing competition for water supplies and rising costs of applying water make efficient irrigation important. Yield and water use of safflower were evaluated on silt loam soil. Defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…The overall average was 305 g/kg, compared to 286 g/kg observed in full irrigation conditions. This result is in disagreement with that found by Nabipour et al [28]. In their study, they observed that seed oil content in safflower was reduced by drought occurring during bloom and maturity stages.…”
Section: Effect Of the Genotype The Environment And Their Interactiocontrasting
confidence: 80%
“…The overall average was 305 g/kg, compared to 286 g/kg observed in full irrigation conditions. This result is in disagreement with that found by Nabipour et al [28]. In their study, they observed that seed oil content in safflower was reduced by drought occurring during bloom and maturity stages.…”
Section: Effect Of the Genotype The Environment And Their Interactiocontrasting
confidence: 80%
“…Results also showed a reduction in oil yield and oil percentage in response to drought which was more impressive for oil yield. A decrease in safflower oil content with rising in drought has been documented reported by Nabipour et al (2007) and Ashrafi and Razmjoo (2010).…”
Section: Resultsmentioning
confidence: 69%
“…Water deficit was reported to reduce yield, yield components and oil content of safflower cultivars [24]. They [24] used normal irrigation or withholding water at budding, flowering and maturity stages. Arak contained the highest oil content followed by Esfahan and FO 2 under stress and non-stress conditions, respectively.…”
Section: Resultsmentioning
confidence: 99%